Design of a Sliding PID Controller for The Surge and Roll Motion Control of UNUSAITS AUV - Teguh Herlambang; Hendro Nurhadi (LPPM Institut Teknologi Sepuluh Nopember, 2017)
The development of underwater vehicle technology is commonly utilized in defences. NKRI needs this technology for applications and multifunctional technology becomes an important thing, since its modernization leads to developed AUV as Republics-of-Indonesia’s main weapon is sea defence. This paper proposes motion control system design applying equation of motion with 2 Degree of Freedom (DOF) to AUV system. The equation of AUV motion with 2-DOF covers surge motion and rolling motion is in the form of nonlinear equation. The control system design applied to the system of UNUSAITS AUV uses method of Sliding Proportional Integral Derivative (SPID). The result of SPID control system with the equation of motion with 2-DOF suggested that the stability of the system was reached when the resulted errors on surge motion and rolling motion were respectively 0.002% and 0.05%.